Elementos estéticos no design automotivo e sua influência na percepção do usuário: uma análise do ponto de vista do repertório pessoal - Demaison, André Leonardo [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The automotive industry is among the ones that move the world economy the most. More than a means of transportation, the automobile has uniquely transformed the organization of society since the beginning of its production on an industrial scale and has become a status symbol. Cars are at the center of important current discussions, such as urban mobility, diversification of the energy matrix, emission of pollutants and causes of accidents. They are, therefore, one of the most relevant products in the contemporary world and they’re widely studied from the Design perspective. In this way, this research analyzed, from the user's point of view, the relationship between the subject and the object, in order to understand the effect of aesthetic and symbolic elements in the functional perception of the product, using the automobile as a case study. Initially, a Semantic Differential questionnaire was applied with 109 participants of different levels of enthusiasm in relation to automobiles, which allowed us to observe how users identify practical functions from the images of 24 models in five categories. In addition, the questionnaire allowed the selection of five vehicles for the application of the Repertory Grid Technique method (KELLY, 1955) with two different groups: 10 participants considered “specialists” in automobiles and 10 considered “nonspecialists”. With the method, it was possible to understand how users perceive the cars use functions from the aesthetic and symbolic factors attributed to the product. To support the research, studies about Automotive Design and concepts related to Emotional Design (NORMAN, 2008) and the "wow! factor" (DESMET, PORCELIJN and VAN DIJK, 2005) were used on it. This thesis also presents a brief chronology of automotive design and a proposal for the classification of automobiles. From the analysis of the results, it is concluded that the use function of the selected car models are clearly identified by the users by observing the aesthetic elements. However, there is a significant difference in the way the groups view automobiles: “Specialists” are more concerned with practical aspects, while symbolic factors appear more relevantly in the personal repertory of the “Non-specialists” users.

A indústria automotiva está entre as que mais movimentam a economia mundial. Mais do que um meio de transporte, o automóvel transformou de forma ímpar a organização da sociedade desde o início de sua produção em escala industrial e tornou-se símbolo de status. Os carros estão no centro de importantes discussões atuais, como mobilidade urbana, diversificação da matriz energética, emissão de poluentes e causas de acidentes. Trata-se, portanto, de um dos produtos mais relevantes no mundo contemporâneo e bastante estudado sob a ótica do Design. Diante disso, a presente pesquisa analisou, do ponto de vista do usuário, a relação entre o sujeito e o objeto, a fim de compreender o efeito dos elementos estéticos e simbólicos na percepção funcional do produto, utilizando o automóvel como estudo de caso. Inicialmente foi aplicado um questionário de Diferencial Semântico com 109 participantes de diferentes níveis de entusiasmo em relação a automóveis, o que permitiu observar como usuários identificam as funções práticas a partir das imagens de 24 modelos de cinco categorias. Além disso, o questionário possibilitou a seleção de cinco automóveis para a aplicação do método Repertory Grid Technique (KELLY, 1955) com dois diferentes grupos: 10 participantes considerados “especialistas” em automóveis e 10 considerados “não-especialistas”. Com o método, foi possível compreender como os usuários percebem as funções de uso dos automóveis a partir dos fatores estéticos e simbólicos atribuídos ao produto. Para embasar a pesquisa, foram utilizados estudos sobre o Design Automotivo e conceitos relacionados ao Design Emocional (NORMAN, 2008) e ao “fator wow!” (DESMET, PORCELIJN e VAN DIJK, 2005). Esta tese apresenta, ainda, uma breve cronologia do design automotivo e uma proposta de classificação dos automóveis. A partir da análise dos resultados, concluiu-se que as funções de uso dos modelos selecionados são claramente identificadas pelos usuários pela observação dos elementos estéticos. No entanto, há uma significativa diferença na forma como os grupos enxergam os automóveis: “Especialistas” atêm-se mais aos aspectos práticos, enquanto os fatores simbólicos aparecem de forma mais relevante no repertório pessoal dos “Não-especialistas”.
Aesthetic elements in automotive design and their influence on user perception: an analysis from the point of view of the personal repertoire
Keywords: Product design; Automotive design; Product functions; User perception; Personal repertoire; Design de produto; Design automotivo; Funções do produto; Percepção do usuário; Repertório pessoal